Explicit Formula is A(n)=9-2(n-1) Recursive Formula is A(1)=9 ; A(n)=A(n-1)-2
Work Step by Step
1. The Explicit Formula is A(n)=9-2(n-1) because the explicit formula uses the formula A(n)=A(1)+(n-1)d and in this case A(1) equals 9 as it is first term in the sequence and d is -2 because the values in the sequence are decreasing by 2. 2. The Recursive Formula is A(1)=9 ; A(n)=A(n-1)-2 because it represents A(n) as the value of the nth term and uses A(n-1) to represent the value of the previous term. The -2 represents the amount with which the nth term differs from the previous term.